Turk J Gastroenterol 2023
DOI: 10.5152/tjg.2023.22193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adherence to Mediterranean Diet on Disease Activity in Patients with Inflammatory Bowel Disease

Abstract: Background/Aims: Mediterranean diet, owing to its inflammation-modulatory effects, is considered a beneficial dietary regimen for patients with inflammatory bowel disease. Despite promising results in the literature, studies on this subject are still limited. Therefore, the aim of this study was to evaluate adherence to the Mediterranean diet in patients with inflammatory bowel disease and examine its impact on disease activity and quality of life. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In patients with UC, adherence to the MD positively influences disease activity and quality of life [15]. Patients with UC with strict adherence to the MD appear to have lower disease activity scores and higher quality of life parameters than those with low adherence [50].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In patients with UC, adherence to the MD positively influences disease activity and quality of life [15]. Patients with UC with strict adherence to the MD appear to have lower disease activity scores and higher quality of life parameters than those with low adherence [50].…”
Section: Discussionmentioning
confidence: 97%
“…The study reported that compared with the healthy population, the most affected SF-36 parameters were vitality, mental health, and emotional health-related parameters [66]. A recent study by Çelik et al discovered that clinical activity was negatively correlated with the SF-36 subparameters of physical role difficulty, emotional role difficulty, vitality, mental health, and general health perception in individuals with IBD [15]. This study is the first RCT to evaluate the effects of an 8-week MD intervention on the health-related quality of life of patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 Mediterranean diets, rich in polyphenols and fiber, are considered a beneficial dietary regimen for IBD. 10 Low dietary fiber promotes mucin-degrading bacteria eroding healthy colon mucus, leading to lethal colitis in IL-10-deficient mice. 49 Western dietary patterns, characterized by high consumption of fats and sugars and a low fiber intake, contribute to the development of IBD, because of the decreased abundance of SCFA-producing bacteria and the increased abundance of pathogens such as Helicobacter trogontum .…”
Section: Disease Pathogenesismentioning
confidence: 99%
“… 7 , 8 Additionally, environmental factors such as lifestyle and diet, play a significant role in the development of IBD, with certain dietary components, like mannose, showing potential for ameliorating colitis. 9 11 IBD pathogenesis is associated with the complex interactions between genetic predispositions, gut microbiome perturbations, environmental factors, and immune response dysregulation.…”
Section: Introductionmentioning
confidence: 99%